Innovation in Digitalization of UI/UX Design with User Centered Design to Increase Customer Satisfaction - Yohana Felicia; Ali Ibrahim; Dwi Rosa Indah; Iin Seprina (Journal of Applied Informatics and Computing)
In the era of rapid digitalization, the economic sector, especially small and medium enterprises, is required to adapt to the development of digitalization. SDS YPMM Cooperative is one example of a small business that still relies on traditional systems in its business processes. To overcome this problem, a website-based User Interface (UI) and User Experience (UX) design was carried out to digitize the SDS YPMM cooperative business process. In the design, the User Centered Design method is used which focuses on user needs. This method is done by Specify the context of use, specify user and organizational requirements, produce design solutions, and evaluate design against user requirements. At the evaluation stage, the System Usability Scale (SUS) was used to measure the level of usability of the resulting design. The evaluation results obtained 179 respondents out of 533 population for the user interface showed a score of 84.97, which falls into the “acceptable” category and a rating of B or “Excellent”. Meanwhile, the admin interface received 5 respondents from 5 populations and scored 93, which falls into the “acceptable” category and an A or “Best Imaginable” rating. These findings indicate that the UI/UX design is highly accepted by both categories of users, thereby improving operational efficiency and shopping experience, which creates satisfaction with SDS YPMM cooperative services.